PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Lutfita, Afifa; Takarini, Nurjanti (Riset Manajemen dan Akuntansi, 2021)
The value of the company is one aspect that is considered by investors before investing their shares. Many factors can affect the value of the company. Therefore, the purpose of this study is to determine the effect of profitability, company size and capital structure on the value of the services companies sub-sector tourism, hotel and restaurant listed on the Indonesia Stock Exchange during the period 2016 to 2019. The population in this study were 37 services companies sub-sector tourism, hotel and restaurant listed on the IDX for the 2016-2019 period with a total research sample of 20 companies. The data collection method used is purposive sampling. This study uses multiple linear regression as a data analysis technique. The results showed that profitability had a positive and significant effect on company value, firm size had a negative and significant effect on company value and capital structure had a positive and significant effect on company value.